Referral pathways for patients with TIA avoiding hospital admission: a scoping review - Bridie Evans (BMJ Open, 2017)
AbstractObjective To identify the features and effects of a pathway for emergency assessment and referral of patients with suspected transient ischaemic attack (TIA) in order to avoid admission to hospital.Design Scoping review.Data sources PubMed, CINAHL Web of Science, Scopus.Study selection Reports of primary research on referral of patients with suspected TIA directly to specialist outpatient services.Data extraction We screened studies for eligibility and extracted data from relevant studies. Data were analysed to describe setting, assessment and referral processes, treatment, implementation and outcomes.Results 8 international studies were identified, mostly cohort designs. 4 pathways were used by family doctors and 3 pathways by emergency department physicians. No pathways used by paramedics were found. Referrals were made to specialist clinic either directly or via a 24-hour helpline. Practitioners identified TIA symptoms and risk of further events using a checklist including the ABCD2 tool or clinical assessment. Antiplatelet medication was often given, usually aspirin unless contraindicated. Some patients underwent tests before referral and discharge. 5 studies reported reduced incident of stroke at 90 days, from 6–10% predicted rate to 1.3–2.1% actual rate. Between 44% and 83% of suspected TIA cases in these studies were referred through the pathways.Conclusions Research literature has focused on assessment and referral by family doctors and ED physicians to reduce hospitalisation of patients with TIA. No pathways for paramedical use were reported. We will use results of this scoping review to inform development of a paramedical referral pathway to be tested in a feasibility trial.Trial registration number ISRCTN85516498. Stage: pre-results.